State Power Supervision and Corruption Prevention in Indonesia: Evaluating Institutional Ineffectiveness through Hisbah Perspectives - Mustafid Mustafid; Mardona Siregar; Imam Agung Prakoso; Putra Halomoan Hsb; Muhammad Faiz Algifari (Tanfizi : Journal of Islamic Constitutional and Political Law, 2026)
This study examines the effectiveness of oversight of power in preventing corruption in Indonesia from the perspective of fiqh siyasah hisbah. Studies on corruption have tended to focus on positive law and modern institutional approaches, while the Islamic ethical-political dimension has not been widely used as an analytical framework in evaluating weak institutional oversight. This article addresses this gap by analyzing how the principles of fiqh siyasah, particularly the concepts of amanah, hisbah, and maslahah, can be used to interpret the structural problems in the oversight of power in Indonesia. This study uses library research with a qualitative-analytical approach through a review of primary sources in the form of the Qur'an, hadith, and classical and contemporary literature on fiqh siyasah, combined with an analysis of regulations, anti-corruption policies, and academic studies on oversight institutions in Indonesia. The results show that the weak effectiveness of oversight institutions is not solely caused by regulatory issues, but also by the dominance of political interests, low elite integrity, and the absence of ethical oversight oriented towards moral accountability. In this context, fiqh siyasah hisbah offers a normative and theoretical framework that places supervision of power as a collective responsibility of the state and society.